Effectiveness of methamphetamine abuse treatment: Predictors of treatment completion and comparison of two residential treatment programs. (1st August 2019) - Kamp, F.; Proebstl, L.; Hager, L.; Schreiber, A.; Riebschläger, M.; Neumann, S.; Straif, M.; Schacht-Jablonowsky, M.; Manz, K.; Soyka, M.; Koller, G.
Highlights: About 60% of German methamphetamine users complete a six month inpatient treatment. A methamphetamine specific treatment is not superior to an unspecialized treatment. History of injection drug use predicts treatment drop-out. Current treatment programs reduce craving and psychiatric symptoms. Abstract: Background: There is an increasing demand of evidence-based treatment options for methamphetamine users, but research in this field is limited. This study therefore evaluates the efficacy of two residential treatment programs for methamphetamine users. Method: A total of 108 patients with a history of methamphetamine abuse from two inpatient rehabilitation centers were studied for psychiatric symptoms, craving, psychosocial resources, and cognitive functioning at the start and end of therapy. Patients from one center ("amphetamine type stimulant group") received conventional group therapy plus an additional 10 h of group therapy focusing on stimulant use. Patients from the other center ("treatment as usual") received conventional group therapy only. Predictors of drop-out were estimated. Results: A drop-out rate of 40.7% was observed without a significant difference between both centers. Patients remained significantly longer in treatment as usual compared to amphetamine type stimulant treatment. Irrespective of treatment program, craving and psychiatric symptoms significantly decreased while psychosocial resources, processing speed, and cognitive flexibility improved over time. Other cognitive measures yielded mixed results. History of injection drug use was a significant predictor for treatment drop-out. Conclusions: Existing treatments are effective in reducing craving and psychiatric symptoms. Additional stimulant specific groups do not appear to influence treatment completion and secondary outcome measures. Institutions should therefore offer treatment for methamphetamine users, even if they do not provide a therapy content focusing on methamphetamine. History of injection drug use should receive attention in treatment to prevent drop-out. Changes in cognitive functioning need to be further explored.